2023
DOI: 10.3390/ma16072887
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Butyl Acrylate Copolymer Emulsion and Its Regulation Effect on Cement Hydration

Abstract: Due to its large volume and poor thermal conductivity, mass concrete is prone to temperature cracking caused by heat release during cement hydration after pouring. To address the issue of temperature cracking in mass concrete, this study utilized emulsion polymerization to prepare polybutyl acrylate (PBA) emulsions. At an optimal dosage of 1.5%, the addition of a PBA emulsion reduced the temperature rise of cement paste by 12.4%. The inhibitory mechanism of a PBA emulsion on cement hydration was analyzed by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Adding polymers reduces the temperature gradient of concrete and the risk of concrete cracking. The heat flow curve of cement hydration is divided into four stages, namely, the initial dissolution stage, induction stage, acceleration stage, and attenuation stage [ 35 , 36 ]. Sifan Li et al [ 37 ] showed that when butyl acrylate (PBA) lotion was added to concrete, the second exothermic peak was mainly concentrated in the cement hydration process, it slowed down due to the increase and decrease rate of PBA addition, and the degree of reduction in the hydration heat peak was positively related to the increase in PBA content ( Figure 1 ).…”
Section: Properties Of Cement-based Materials Modified By Acrylate Lo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adding polymers reduces the temperature gradient of concrete and the risk of concrete cracking. The heat flow curve of cement hydration is divided into four stages, namely, the initial dissolution stage, induction stage, acceleration stage, and attenuation stage [ 35 , 36 ]. Sifan Li et al [ 37 ] showed that when butyl acrylate (PBA) lotion was added to concrete, the second exothermic peak was mainly concentrated in the cement hydration process, it slowed down due to the increase and decrease rate of PBA addition, and the degree of reduction in the hydration heat peak was positively related to the increase in PBA content ( Figure 1 ).…”
Section: Properties Of Cement-based Materials Modified By Acrylate Lo...mentioning
confidence: 99%
“…Ca 2+ and Na + act as a bridge between the functional group oxygen atom of hydrated calcium silicate and the silicate chain oxygen. O-Ca-O and O-Na-O salt bridges enhance interface bonding, suppress crack development, and improve the ductility of cement–polymer composites [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Properties Of Cement-based Materials Modified By Acrylate Lo...mentioning
confidence: 99%
“…Among the polymers commonly used for modification of cement-based materials, most of them are in the form of latex, lotion, or dispersible powder, such as SBR (styrene butadiene rubber), EVA (ethylene vinyl acetate copolymer), and acrylate. Adding these polymers affects cement hydration, the composition and morphology of hydration products, pore structure, and permeability [32,33]. Compared with traditional cementitious materials, many effective polymer-modified mortar systems have improved their performance and expanded their application fields.…”
Section: Introductionmentioning
confidence: 99%